Toxicidade e remoção de arsênio pela cianobactéria: Microcystis novacekii - Fernanda Aires Guedes Ferreira (2013)
The elevated toxicity and potential accumulation of arsenic in different environments have encouraged research methods for removal of these ions from contaminated waters. Cyanobacteria have properties of interaction with metal ions that can be exploited to recover the contaminated areas. To evaluate the potential of these organisms in arsenic removal this study aimed to determine the toxicity and potential removal of arsenate (As V) and arsenite (As III) by the cyanobacterium Microcystis novacekii. Under culture conditions in laboratory cultures of cyanobacteria, exponential growth phase were exposed for 96 hours (toxicity test) and 192 hours (test/removal bioaccumulation) at concentrations of As(V)(Na2HAsO47H 2O) in two concentrations series: 0.05, 0.5, 5 and 50.0 mg.L-1 (low concentrations) and 500, 900; 1620; 2916 and 5250 mg.L-1 (high concentrations). For As (III) (NaAsO2) were evaluated concentrations of 14.7, 26.5, 47.6 and 85.7 mg. L-1. The inhibition of growth was monitored daily by assessing the optical density and the cell count under optical microscope. Quantification of arsenic bio-accumulated in the cell, the mucilage sheath and removed from the aqueous medium was determined by inductively coupled plasma optical emission spectrometry (ICP-OES) after 2, 96 and 192 hours of exposure. The toxicity results show that low concentrations of As(V) no inhibition of the growth of cyanobacteria was recorded compared to control (p> 0.05), while in higher concentrations occurred progressive inhibition of growth. The trivalent form showed stronger toxicity to M. novacekii than the oxidized one. The EC50 values were 40.9 mg.L-1 (As III) and 5,164.8 mg.L-1 (As V). The high resistance to both chemical species tested indicate the need for complementary studies to elucidate the mechanisms of resistance of this cyanobacteria.The arsenic removal tests showed that M. novacekii showed capacity to accumulate arsenic in the trivalent form, regardless the concentration (p> 0.05) metalloid in the aqueous medium, accumulating c. 3 mg.L-1of arsenic. This bioaccumulation potential was however not significant to the oxidized form. Furthermore, the mucilage sheath showed no role in accumulating arsenic. Considering the chemical-physical characteristics described for exo-polysaccharides it is believed that ionized chemical groups exist in this layer which can hinder the approach of anions such as As (V) present in the aqueous medium at neutral pH and H2As and allow the penetration of neutral molecular form of As (III) present in the aqueous medium as H. These presented results may contribute to the understanding of the dynamics of arsenic in the natural environment and its impact on phytoplankton cells, particularly cyanobacteria.